The Livestock Economy of Pakistan: An Agricultural Sector Model Approach (The Pakistan Development Review, 1997)
The Pakistan Agricultural Sector Model (PASM) developed by Davies et al. (1991) was modified to enhance the livestock sub-sector. Nutrient-based rations replaced feedstuff-based rations and dry matter minimum and maximum constraints (stomach capacity) were added. Several initial simulations were undertaken to examine the structure of the modified model and its impact across the crop and livestock sub-sectors. These simulations included relaxing exogenous livestock numbers and selected crop hectarage constraints, and requiring that green forage be fed in the season grown. Most importantly, the results demonstrated that fodder hectarage will grow with livestock numbers to insure that sufficient green forage is available seasonally. Two other analyses were performed to demonstrate the need to specify linkages between the crop and livestock sub-sectors. An analysis of transforming the livestock sub-sector from traditional to feedlot-based technology demonstrated that the reduced numbers of non-milking cattle needed for a given output of meat would provide the potential for increased production of various crops and other livestock products. Also, expanded cotton and Irri rice exports, hypothesised to occur through trade liberalisation from the Uruguay Round of the GATT, highlighted other inter-relationships between the crop and livestock sub-sectors. Greater production of both livestock and other crops might accompany the expansion of cotton production but less livestock feed would be available with expanded exports of Irri rice.